Requirement and Application Frequencies of Nitrogen Fertilizer on Bread Wheat Variety, Arpathan-9 - DOGAN, RAMAZAN; CELIK, NECMETTIN; YURUR, NEVZAT (Asian Journal of Chemistry, 2010)
The split application of nitrogen required by wheat for seed yield was more advantageous than single application. But the frequencies of nitrogen application is not clear and depends especially on rain and irrigational conditions. On the other hand, nitrogen requirement of a variety varies depending on its genetic yield potential and the environmental conditions. In this study, the effects of increasing amounts of nitrogen and their application frequencies on the seed yield and yield components of a bread wheat variety, Arpathan-9, were investigated under ecological condition of submediterranean climate. The experimental results indicated that increasing amount of nitrogen significantly affected the grain yield of the variety. The highest seed yields were obtained from plots to which 120, 160 and 200 kg N ha-1 were applied. Applying the halves of different nitrogen amounts at one or two different times made no significance when seed yield was considered. Seed yield components determined in this study were also significantly affected by nitrogen fertilizer levels in the same way as seed yield. Applying the half of each level of nitrogen fertilizer at one and two time had no effect neither on seed yield nor on seed yield components.